2017
DOI: 10.1016/j.mineng.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the width of particle size distribution to improve pressure filtration properties of slurries

Abstract: The filtration properties of mineral slurries depend for instance on the properties of the solid particles and on the way how these particles arrange themselves when the filter cake is formed. In cake filtration applications, the focus is often on particle size instead of the shape of particle size distribution (PSD). The aim of this experimental study is to demonstrate the influence of the width of PSD on the properties of the filter cake in the pressure filtration of Ni-Cu mine tailings. Modification of PSD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 20 publications
0
12
1
Order By: Relevance
“…However, the trend of porosity against the span is slightly decreasing for the higher filtration pressures (300 and 500 kPa). Previous literature on the topic (Kinnarinen et al, 2015;Kinnarinen et al, 2017) shows clearer than the present results that a narrow particle size distribution usually results in higher cake porosities.…”
Section: Pressure Filtration Properties Of the Streamscontrasting
confidence: 85%
See 1 more Smart Citation
“…However, the trend of porosity against the span is slightly decreasing for the higher filtration pressures (300 and 500 kPa). Previous literature on the topic (Kinnarinen et al, 2015;Kinnarinen et al, 2017) shows clearer than the present results that a narrow particle size distribution usually results in higher cake porosities.…”
Section: Pressure Filtration Properties Of the Streamscontrasting
confidence: 85%
“…It has been reported in the literature (e.g. Kinnarinen et al, 2017) that reduction of the width of the distribution to produce a more porous cake would facilitate the filtration in some cases, in spite of the reduction of particle size.…”
Section: Introductionmentioning
confidence: 99%
“…Kinnarinen et al [15] further suggested that although a wider PSD assists in the filterability, decreasing the wideness of particle size might help overcome the adverse impact on the flux caused by tiny particles. This is because, for a particularly narrow particle size distribution, the formation of more or less an unrestricted cake structure results in lesser resistance to fluid passage.…”
Section: Effect Of Particle Size and Particle Size Distribution On Filtrationmentioning
confidence: 99%
“…The average specific cake resistance α av for the constant pressure of filtration was calculated using experimental data and equations based on Darcy's law (Equation 3). The procedure of determining α av from experimental data is widely applied, and has been introduced in the literature [31,32]. The integrated form of the general filtration equation (Equation 3) is given by:…”
Section: Filtration Measurementsmentioning
confidence: 99%